Broxtowe 2.0: using CRM and Web 2.0 as a catalyst for service (re)design in order to improve citizen engagement - Albregt, Robin (2010)
This report examines how Customer Relationship Management and Web 2.0 can act as a catalyst for service (re)design in order to improve citizen engagement at Broxtowe Borough Council. Its department for Waste and Recycling Management has been used as the case study environment.